2020
DOI: 10.1525/001c.17242
|View full text |Cite|
|
Sign up to set email alerts
|

Streaming Media’s Environmental Impact

Abstract: This group of articles, which arose from a panel planned for the 2020 annual meeting of members of the Society for Cinema and Media Studies, draws attention to an unpopular but inescapable issue: the adverse environmental effects of streaming media. Four of these brief interventions focus on streaming media's carbon footprint, estimated by some to be 1 percent of global greenhouse gas emissions (The Shift Project 2019). This startling figure is rising at a calamitous rate as more people around the world stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…According in CO 2 emissions year after year. In a similar study conducted by Marks et al, (2020) streaming online data is responsible for 58-60 percent of internet traffic and emits 300 million tons of carbon dioxide every year, which roughly adds up to 1 percent of overall emissions (First 2022) BBC reported that 58 percent of all downstream traffic on the internet is video, followed by web browsing at 17 percent, gaming at 7.8 percent, and social media at 5.1 percent [9]. Other forms of media streaming include YouTube, 11.4 percent, embedded video on Webpages 13.1 percent and web searching 7.8 percent [15].…”
Section: Digital Carbon Footprintmentioning
confidence: 76%
See 1 more Smart Citation
“…According in CO 2 emissions year after year. In a similar study conducted by Marks et al, (2020) streaming online data is responsible for 58-60 percent of internet traffic and emits 300 million tons of carbon dioxide every year, which roughly adds up to 1 percent of overall emissions (First 2022) BBC reported that 58 percent of all downstream traffic on the internet is video, followed by web browsing at 17 percent, gaming at 7.8 percent, and social media at 5.1 percent [9]. Other forms of media streaming include YouTube, 11.4 percent, embedded video on Webpages 13.1 percent and web searching 7.8 percent [15].…”
Section: Digital Carbon Footprintmentioning
confidence: 76%
“…As a matter of fact, digital technologies' energy utilization increased by nearly 70 percent between 2013 and 2020 Fig. shows the absolute CO 2 emissions of all snaps, transferred or sent, in the year 2015 [9]. Facebook, Instagram, and WhatsApp have 80 million, 350 million, and 4.5 billion pictures per day, a remarkable amount of data with a huge impact in terms of CO 2 emissions, which increases every year [10].…”
Section: Introductionmentioning
confidence: 99%
“…This research results in interest for critical questions pertaining to issues of power such as labor, discrimination, exploitation, and surveillance. We now also increasingly encounter studies exploring the adverse environmental (material) effects of streaming media (Lobato 2019;Marks et al 2020) and prompts for intensifying such concerns in environmental media studies or green(ing) media studies (Keilbach and Pabiś-Orzeszyna 2022).…”
Section: Approaching Data Criticallymentioning
confidence: 99%
“…Poszerzające podejście do tematu prezentuje monografia Streaming media's environmental impact [Marks et al 2020]. Zwraca uwagę na niepopularny, ale nieunikniony problem niekorzystnego wpływu mediów strumieniowych (czyli działających na zasadzie jednoczesnego przesyłania i odbioru danych audio i wideo za pomocą sieci komputerowej) na środowisko.…”
Section: W Stronę Zielonej Produkcji Filmowej -Między Sceptycyzmem a ...unclassified